2005
DOI: 10.1097/01.brs.0000148048.15348.9b
|View full text |Cite
|
Sign up to set email alerts
|

A Slowly Progressive and Reproducible Animal Model of Intervertebral Disc Degeneration Characterized by MRI, X-Ray, and Histology

Abstract: Stabbing the anterolateral anulus fibrosus of adult rabbit lumbar discs with a 16-gauge hypodermic needle to a limited (5-mm) depth results in a number of slowly progressive and reproducible magnetic resonance imaging, radiograph, and histologic changes over 24 weeks that show a similarity to changes seen in human intervertebral disc degeneration. This model would appear suitable for studying pathogenesis and pathophysiology of intervertebral disc degeneration and testing safety and efficacy of novel treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
248
2
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(281 citation statements)
references
References 21 publications
23
248
2
8
Order By: Relevance
“…This lack of mechanical consequence indicates that a 33-gauge needle may prove suitable for administering developmental therapies to the nucleus pulposus of rat intervertebral discs, whereas a larger gauge needle may create an altered mechanical environment and initiate degeneration. [40][41][42] Nucleus glycosaminoglycan content was linearly correlated with neutral zone properties, while the elastic stiffness at high magnitudes of both compression and tension were not dependent upon nucleus glycosaminoglycan content. Thus, glycosaminoglycan depletion results in a state of hypermobility at relatively low applied loads.…”
Section: Discussionmentioning
confidence: 93%
“…This lack of mechanical consequence indicates that a 33-gauge needle may prove suitable for administering developmental therapies to the nucleus pulposus of rat intervertebral discs, whereas a larger gauge needle may create an altered mechanical environment and initiate degeneration. [40][41][42] Nucleus glycosaminoglycan content was linearly correlated with neutral zone properties, while the elastic stiffness at high magnitudes of both compression and tension were not dependent upon nucleus glycosaminoglycan content. Thus, glycosaminoglycan depletion results in a state of hypermobility at relatively low applied loads.…”
Section: Discussionmentioning
confidence: 93%
“…[13][14][15][16][17] It is generally believed that needle puncture injury with small-gauge needles is not expected to cause damage, whereas needle puncture injury with large-gauge needles leads to degenerative changes. AF needle puncture injury to the disc in rabbits using needles of different gauges has been demonstrated to result in slow progressive degeneration as measured using magnetic resonance imaging (MRI), radiograph, histology, and polymerase chain reaction.…”
mentioning
confidence: 99%
“…Rat caudal discs are used in this study because of the substantial and growing body of in vivo and ex vivo mechanobiology research using small animals (e.g. rabbits, rats, and mice) (Iatridis et al, 1999;Gruber et al, 2002;Ching et al, 2003;Hsieh and Lotz, 2003;Norcross et al, 2003;Risbud et al, 2003;Maclean et al, 2004;An et al, 2005;Kim et al, 2005;Sobajima et al, 2005). It was recently reported that mouse lumbar discs matched the previously reported nonlinear response of human lumbar discs while mouse caudal discs only matched the linear response provided differences in cross-sectional areas were accounted for (Sarver and Elliott, 2005).…”
Section: Introductionmentioning
confidence: 66%